Health Systems and Patient-related Factors Contributing to Late Antenatal Care Attendance among Pregnant Women in Limpopo Province, South Africa - Ntuli, Thembelihle Sam; Matlala, France; Raesebe Johanna, Mokolome; Mokoena, Oratilwe Penwell (Babali Publisher, 2024)
Background: Antenatal care is a maternal health service provided throughout pregnancy to identify risks of complications and reduce maternal and perinatal mortality. The study aimed to assess the prevalence and reasons for the late initiation of antenatal care. Methods: A facility-based cross-sectional study was conducted at three primary healthcare centres in Limpopo province, South Africa, from October to November 2020. A consecutive sample of 231 pregnant women who received antenatal care during the data collection period participated in the study. Data analysis was performed using SPSS version 25. Results: The findings indicate that 43.12% of the women initiated antenatal care late. The most common reasons for late initiation included lack of information, cultural beliefs, distance to the facility, waiting times, and the operating hours of the facility. Conclusion: There is an urgent need to develop and implement educational programs for antenatal care, strengthen community-based services, and evaluate staff workload at the study sites.